2011
DOI: 10.1007/s13239-011-0041-y
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Fluid Shear Stresses in Capillary Sprouts

Abstract: Fluid shear stress has been implicated as a regulator of sprouting angiogenesis. However, whether endothelial cells within capillary sprouts in vivo experience physiologically relevant shear stresses remains unclear. The objective of our study is to estimate the shear stress distribution along the length of a capillary sprout through computational modeling of blood flow in a blind-ended channel branching off a host vessel. In this model, we use sprout geometries typical for the rat mesenteric microvasculature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 40 publications
(51 reference statements)
2
29
0
Order By: Relevance
“…The level of shear stress for human aorta is 10–20 dyne/cm 2 and for walls of veins is 1–6 dyne/cm 2 [ 23 ]. For single sprouts, wall shear stress is reported to be around 10 dyne/cm 2 or less [ 64 ]. The shear stress has its maximum value in the junction area with parent vessel and decreases along the sprout [ 64 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of shear stress for human aorta is 10–20 dyne/cm 2 and for walls of veins is 1–6 dyne/cm 2 [ 23 ]. For single sprouts, wall shear stress is reported to be around 10 dyne/cm 2 or less [ 64 ]. The shear stress has its maximum value in the junction area with parent vessel and decreases along the sprout [ 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…For single sprouts, wall shear stress is reported to be around 10 dyne/cm 2 or less [ 64 ]. The shear stress has its maximum value in the junction area with parent vessel and decreases along the sprout [ 64 ]. This shear is due to blood flow in parent vessel and leakiness of the newly formed capillaries.…”
Section: Methodsmentioning
confidence: 99%
“…These questions are difficult to answer experimentally because of technical challenges associated with intravital measurement of flow profiles within a sprout. Stapor et al [41] recently used a computational fluid dynamic approach to estimate the shear stress distribution along a blind-ended experimental observations computational models Do hypertensive microvascular networks have increased resistance? Do endothelial cells experience shear stress during capillary sprouting?…”
Section: Vessel Level: Do Endothelial Cells Experience Shear Stress Dmentioning
confidence: 99%
“…Logically, RBC flow by the entrance of a blind-ended sprout or even within a sprout would impact local shear stress and shear stress gradient magnitudes. Indeed, Stapor et al [41] suggested that RBC flow within a host vessel resulted in local maximum magnitudes at the sprout entrance. RBC plugging of the sprout served to shorten the effective sprout length and similarly influenced magnitudes depending on the wall permeability scenario.…”
Section: Cell Levelmentioning
confidence: 99%
“…ECs are activated by shear stress magnitudes as low as 0.2 dyne/cm 2 [15,69]. Activation means that both integrin and RTK are activated and this does not depend on their specific ligands [1,31]; however, activation of RTK and integrin depends on the activation of VE-cadherin [2].…”
Section: Cell Phenotype Alteration Due To Flow In the Loopmentioning
confidence: 99%